The cultural competence of nurses and its relationship to socio-demographic factors: a cross-sectional survey - Rita Urbanavičė; Rabie Adel El Arab; Donatas Austys; Marija Skvarčevskaja; Natalja Istomina (BMC Nursing)
Abstract Introduction Escalating migration flows necessitate an intensified focus on the cultural competence of nurses, as culturally competent care is critical for accurately assessing and addressing the needs of patients from diverse backgrounds. Despite its importance, the cultural competence of nurses remains suboptimal and is influenced by various socio-demographic factors. Aim To evaluate the cultural competence of nurses in Lithuania and examine its relationship with socio-demographic characteristics. Methods A cross-sectional survey was conducted among 1,278 nurses across primary, secondary, and tertiary healthcare institutions in Lithuania’s public and private sectors. Cultural competence was assessed using the Nurse Cultural Competence Scale, and statistical analyses were performed to compare competence levels and determine associations with socio-demographic factors. Results Overall, 97.2% of nurses rated their cultural competence as moderate, with only 17.0% attaining a high level (mean score 3.51 ± 0.07; total score 102.88 ± 23.35). The highest scores were observed in the Cultural Awareness (3.94 ± 0.16) and Cultural Sensitivity (3.70 ± 0.28) subscales, while Cultural Knowledge (3.30 ± 0.23) and Cultural Skills (3.22 ± 0.28) were lower. High cultural competence was significantly associated with younger age, university education, proficiency in foreign languages, specialized training, employment in the private healthcare sector, work in urban or rural areas, shorter work experience, and clinical experience with asylum seekers and refugees (p < 0.05). Conclusions The findings indicate that Lithuanian nurses demonstrate moderate cultural competence, with marked deficits in theoretical knowledge and practical skills. This underscores the imperative for enhanced cultural training, indicating that cultural training is necessary to improve the cultural competence of nurses. Clinical trial number Not applicable.